Basic knowledge and attitudes towards biostatistics in sixth- and seventh-year medical students - Vanessa A. Araoz-Melgarejo, Brandon Muñoz Espinoza, Dante M. Quiñones-Laveriano, Jhony A. De La Cruz-Vargas (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Introduction: Biostatistics is essential for evidence-based decision making. Objective: To assess basic knowledge and attitudes towards biostatistics in senior medical students and to find correlated factors. Methods: Cross-sectional, analytical, observational study. A total of 202 students were surveyed virtually. Attitudes towards biostatistics were measured using the Survey of Attitudes Toward Statistics-28 and basic knowledge of statistics using the Novack questionnaire. The covariables were sex, age, academic year, medical internship, having taken an extracurricular course in biostatistics, use of statistical software, intention to do a residency, and medical specialty. Correlation coefficients and score differences were found and, for multivariate analysis, adjusted regression coefficients (β) with 95%CI were found, using p<0.05 as statistically significant. Results: 57.9% of respondents were female and the median age was 25 years. The median and interquartile range of the basic knowledge score was 3 (1-4) and attitude towards biostatistics was 4.6 (4.2-5.0). The factors correlated (adjusted β [95%CI]) to better knowledge consisted of taking an extracurricular biostatistics course (0.65[0.07-1.24]) and higher score on the value subscale (SV) of attitude towards biostatistics (0.33[0.06-0.61]); while for attitude towards biostatistics, older age (0.04[0.01-0.07]) and handling of statistical software (0.31[0.12-0.51]). Conclusions: The level of basic knowledge of biostatistics is low, and correlates with taking an extracurricular course and SV of attitude towards biostatistics. Attitude was positive and correlated with age and the use of statistical software.